Detection algorithm for faulty contact joints in electrical network - Soldatov, А.I.; Soldatov, A.A.; Kostina, M.A.; Abouellail, A.A.; Bortalevich, S.I. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The article proposes a thermoelectric method for monitoring the contact resistance of contact joints in power grids. It describes an algorithm to detect faulty contact joints with resistance exceeding the value specified in regulatory standards. The algorithm is considered using the example of a circuit containing five contact joints and three electrical installations. The algorithm is based on calculating contact resistance from the measured values of thermoelectromotive force and flowing current only at the moment the electrical installation is turned on, which makes it possible to calculate the resistance of the contact through which the electrical installation is connected. By the number of electrical installations being turned on or off, the numbers of the contact joints that make up the power supply circuit of this installation are determined.
Keywords: сontact joint; power supply network; thermoelectromotive force; algorithm